Vocal fold paresis: a review of clinical presentation, differential diagnosis, and prognostic indicators. Issue 3 (June 2016) - Syamal, Mausumi N.; Benninger, Michael S.
Abstract : Purpose of review: Vocal fold paresis is a complex, controversial, and unique clinical entity. Guidance in assessing and evaluating these patients is provided in this comprehensive review of the current literature discussing the varying clinical presentation, the broad differential and general prognosis. Recent findings: Patients with vocal fold paresis can present with elements of hyperfunction, which can often mask an underlying paresis. As such, repetitive phonatory tasks and videostroboscopic examination are critical for the assessment of patients with a suspected paresis. When analyzing stroboscopic findings, anatomical and motion asymmetries can strongly suggest the presence of a paresis. However, it is important to remember that other disorders can sometimes mimic or create a visual asymmetry when a true paresis may not be present. Laryngeal electromyography (LEMG) can serve as a valuable adjunct to confirm a paresis with the most reliable indicator being a decreased recruitment pattern. The differential is vast, including infectious, iatrogenic, systemic rheumatologic, and neurologic conditions. LEMG along with time of onset and the underlying cause of the paresis can be valuable prognostic indicators. Summary: Patients with paresis often present with symptoms of a hyperkinetic voice disorder. Regardless of the myriad of causes, their assessment hinges upon close clinical evaluation with videostroboscopy aided with LEMG.